Nesting ecology of Baya Weaver (Ploceus philippinus Linn. 1766) in selected areas of Perlis and Selangor - Thiruvenggadam, Thiruvinothini (2020)
In Malaysia, Baya Weaver is protected under the country’s Wildlife Conservation Act 2010. Baya Weavers nests can be commonly sighted in agricultural and grassland areas in Malaysia but little study thus far has been conducted locally to understand its nesting ecology and nest structure. During breeding seasons, female Baya Weavers inspect the incomplete nest built by the male birds before choosing the ideal nest for reproductive purposes. The chosen nests by female Baya Weavers are indicated by its completed structure by male Baya Weavers. The objectives of this research were to examine factors affecting the nesting tree selection of the Baya Weaver, to identify the structure of a nest that is important for a female Baya Weaver’s choice for egg-laying, and to examine the effect of climatic factors on the nest structure. A total of eight study sites were chosen to represent the northern (Perlis) and southern regions (Selangor) of Malaysia. A total of 34 complete nests and 12 incomplete nests from Selangor and 32 complete nests and 15 incomplete nests from Perlis were observed and measured from August 2018 to April 2019. The study showed that there were no specific tree species that contributed to the nest tree selection of Baya Weavers, and the height of trees was a contributing nest tree selection factor in Perlis. The size of the egg chamber, nest suspension length and branch thickness were significantly different between complete and incomplete nests in Selangor (Mann-Whitney U, p < 0.05) while only the size of egg chamber showed significant differences between complete and incomplete nests in Perlis (Mann-Whitney U, p < 0.05). This showed that the size of the egg chamber played a role in female Baya Weaver’s nest choice in both states. The microclimate inside and outside the nest varied in both states wherein Selangor study sites, the temperature and light intensity varied inside and outside the nest, and in Perlis study sites the light intensity and humidity varied inside and outside the nest. The results of this study showed that the height of nesting trees, size of the egg chamber and nest climatic factors influence the nesting ecology of Baya Weavers in the study sites of Selangor and Perlis.